Gen Z Investor Behavior: Analyzing the Influence of Sustainable Investment Practices, Financial Education, and Risk Tolerance in Indonesia - Loso Judijanto; Eva Yuniarti Utami; Ade Onny Siagian (Journal of Management and Bussines (JOMB), 2024)
This research analyzes G Z's investment behavior in Indonesia with a focus on sustainable investment practices, financial education and risk tolerance. The research methods used include online surveys and in-depth interviews with a representative sample of Gen Z in Indonesia. The research results show that most Gen Z tend to choose sustainable investments that align with their values, although varying levels of financial literacy influence their understanding of investment products. Additionally, Gen Z individuals' risk tolerance is influenced by their personal experiences, level of education, and social environmental influences. In conclusion, this research provides a holistic picture of the complex interactions between sustainable investment practices, financial literacy, and risk tolerance in the context of Gen Z in Indonesia. Practical implications of these findings are also presented to help stakeholders in the world of finance understand and respond to investment behavior that is increasingly relevant for future generations. Keywords: Financial Education, Gen Z Investment Behavior, Sustainable Investment Practices, Risk Tolerance